Robot-Assisted Laparoscopic Living Donor Nephrectomy: The University of Florence Technique - Serni, Sergio; Pecoraro, Alessio; Sessa, Francesco; Gemma, Luca; Greco, Isabella; Barzaghi, Paolo; Grosso, Antonio Andrea; Corti, Francesco; Mormile, Nicola; Spatafora, Pietro; Caroassai, Simone; Berni, Alessandro; et al. (Frontiers in Surgery, 2021)
To provide a step-by-step overview of the University of Florence technique for robotic living donor nephrectomy (LDN), focusing on its technical nuances and perioperative outcomes. A dedicated robotic LDN program at our Institution was codified in 2012. Data from patients undergoing robotic LDN from 2012 to 2019 were prospectively collected. All robotic LDNs were performed by a highly experienced surgeon, using the da Vinci Si robotic platform in a three-arm configuration. In this report we provide a detailed overview of our surgical technique for robotic LDN. The main objective of the study was to evaluate the technical feasibility and safety of the technique, including perioperative surgical complications rate and mid-term functional outcomes. Overall, 36 patients undergoing robotic LDNs were included in the study. Of these, 28 (78%) were left LDNs. Median (IQR) donor preoperative eGFR was 88 (75.6-90) ml/min/1.73 m2. In all cases, robotic LDN was completed without need of conversion. The median (IQR) overall operative time was 230 (195-258) minutes, while the median console time was 133 (IQR 117-166) min. The median (IQR) warm ischemia time was 175 (140-255) seconds. No intraoperative adverse events or 90-d major surgical complications were recorded. At a median (IQR) follow-up of 24 months (IQR 11-46), median (IQR) eGFR patients undergoing in living donor nephrectomy was 57.4 (47.9; 63.9) ml/min/1.73 m2. In our experience, robotic LDN is technically feasible and safe. The use of robotic surgery for LDN may provide distinct advantages for surgeons while ensuring optimal donors’ perioperative and functional outcomes